Authority of the Election Organizer Ethics Council (DKPP) of the Republic of Indonesia in Canceling the General Election Commission (KPU) Decree Number: 161-PKE-DKPP/XI/2020 - Abdullah Adam; Nam Rumkel; Abdul Aziz Hakim (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This study aims to determine the legal and financial basis of the Honorary Board of Election Organizers (DKPP) of the Republic of Indonesia in canceling the General Election Commission (KPU) Decree. The type of research used by the author is normative law research using normative case studies in the form of legal behavior products. The results of the study show that the position of the Honorary Council of General Election Organizers (DKPP) of the Republic of Indonesia is in the completion of the General Election. The Duties, Authorities and Obligations of the DKPP are regulated in Article 159 paragraph (1), paragraph (2), and paragraph (3) of Law Number 7 of 2017 which states that the DKPP has the authority to summon Election Organizers who are suspected of violating the code of ethics to provide an explanation and defense.